Konsepsi Dasar Ekonomi Mikro Berbasis Paradigmatik Hukum Ekonomi Syariah - Yunus, Muhammad; Athoillah, Mohamad Anton (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
Islamic economics is believed to be a science that exists as an alternative to conventional economics which has failed to develop human welfare in general. Conventional economics is considered to have been born out of a vacuum and there is no role for Islamic scholarship in its historical development, as stated by Schumpeter in his great gap. Scientists emphatically argue that Greco-Hellenistic scholarship reaches the hands of modern European scholars today through the kindness of the hands of Muslims who modify it and add value to it, as stated by Mehdi Nakosteen. Therefore, it is important to explore the existence of conventional economic conceptions in classical Islamic literature. To prove that Conventional Economics does not depart from a vacuum and that Islamic Economics is part of the history of the birth of conventional economics. In several classical Islamic sources, several basic concepts of conventional economics are found which are not only similar but also exactly the same as a whole. In classical Islamic literature, basic concepts such as unlimited human needs, the concept of value, the concept of production, the theory of supply and demand, the mechanism of market prices and others are found. This provides evidence for us that Islamic economics is not a